Efficacy of Mycophenolate Mofetil (Mmf) in the Treatment of Chronic Plaque Type Psoriasis (Journal of Chittagong Medical College Teachers' Association, 2012)
One to two percent of world population is suffering from psoriasis and treating moderate and severe psoriasis is a huge challenge as most of the systemic anti-psoriatics cause long term toxicities. The aim of the study was to see the efficacy and of Mycophenolate mofetil (MMF) in the treatment of moderate to severe plaque type psoriasis. It was an open prospective study conducted in the department of Dermatology and Venereology, Dhaka Medical College, Dhaka and Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka. Seven patients with moderate to severe plaque type psoriasis were treated with MMF 1gm twice daily for twelve weeks. Outcome was measured with Psoriasis Area and Severity Index (PASI) and adverse effects were recorded. Baseline PASI was 10.8 to 30 and PASI reduction after 4, 8 and 12 weeks treatment was 23.70% to 43.75%, 49.5% to 70.37% and 75.0% to 88.89% respectively. PASI-75 (PASI reduction >75.0% was achieved in all seven cases. No adverse effect was found. Mycophenolate Mofetil (MMF) is a effective treatment option for moderate to severe plaque type psoriasis.JCMCTA 2012; 23(1): 46-48